Bone Mineral Density in Schizophrenia: An Update of Current Meta-Analysis and Literature Review Under Guideline of PRISMA - Tseng, Ping-Tao (Medicine (Baltimore), 2015)
Numerous reports have discussed bone mineral density (BMD) or the risk of osteoporosis in schizophrenia, but have yielded only controversial results. We conducted an update of meta-analysis to examine the overall change in BMD in patients with schizophrenia and the effect on BMD of different antipsychotic drugs. Electronic research through platform of PubMed. The inclusion criteria were as follows: articles with relevance to comparisons of BMD in patients with schizophrenia (SCHIZ) and healthy controls (HCs), or articles discussing comparisons of BMD in SCHIZ receiving prolactin-raising (PR) and prolactin-sparing (PS) antipsychotics; articles about clinical trials. In the current meta-analysis, we used the random-effect model to pool the results from 13 studies comparing BMD in SCHIZ and in HCs, and the results from 7 studies comparing BMD in patients receiving PR and PS. Our results revealed significantly lower BMD in SCHIZ than in HCs (P < 0.001). In the meta-regression, mean age of subjects modulated the difference in BMD between patients and control subjects (P < 0.001). In addition, the BMD in SCHIZ taking PR was significantly lower than in those taking PS (P = 0.006). Our study can only point to the phenomenon that BMD in SCHIZ is lower than that in HCs, and cannot reveal any possible pathophysiology or mechanism of this phenomenon. In addition, we could not rule out the possible effect of medication on BMD based on the results of the meta-analysis of comparison of BMD in SCHIZ receiving PR and PS. The main result of our meta-analysis suggests that BMD is significantly lower in SCHIZ than in HCs. Our study emphasizes the importance of further screening for the risk of osteoporosis in young-aged schizophrenic patients, especially those taking PR, which are in high risk of fracture.